EDUKASI BAGAIMANA MENGATUR KEMANDIRIAN PADA LANJUT USIA DI RT 16 RW 04 KELURAHAN RAWA BUAYA JAKARTA BARAT - Desnita Fitri (Sekolah Tinggi Ilmu Kesehatan Kesetiakawanan Sosial Indonesia, 2020)
The aging process results in physical and mental changes, which can affect health and social conditions. These changes greatly affect the independence of the elderly in carrying out activities of daily living. Elderly independence is a behavior that is seen from the way the elderly behave towards themselves and the environment related to their ability to carry out health and social activities. The elderly also need to be taught to be able to stay productive and not depend on others so that their bodies can still carry out activities as usual. Therefore, it is necessary to hold an educational outreach regarding how to regulate independence in the elderly in RT 16, Rawa Buaya Village, West Jakarta.